Controlling mechanism of coal chemical structure on biological gas production characteristics. (29th February 2020) - Gao, Zhixiang; Guo, Hongyu; Liu, Xile; Wang, Qian; Lv, Jinghui; Liu, Sen; Yu, Hongfei; Yin, Xiangju
Summary: To find the effect of coal chemical structure on biogas production, Lignite B was collected and extracted with nitrogen methylpyrrolidone (NMP), acetone and 0.60 mol/L NaOH. Simultaneously, methanogenic bacteria were enriched, and gas production experiments involving solvent extraction from residual coal and secondary gas production experiments involving coal were performed. The characteristics of biogas production, microcrystalline structure and coal chemical structure were analyzed. The results showed that the biogas production capacity of residual coal extracted by different solvents differed. The biogas production capacity of residual coal extracted by 0.60 mol/L NaOH was severely inhibited. The biogas production capacity of residual coal extracted by NMP and acetone was enhanced compared with that of raw coal. In contrast, primary residual coal still exhibits potential for methane production, but the methane production efficiency was reduced. Changes in the microcrystalline structure and functional groups of residual coal showed that solvent extraction increases the spacing and stacking height of the aromatic lamellae of coal, reduces the hydroxyl, methyl, methylene and aromatic hydrocarbon levels in coal, loosens the macromolecular network structure of coal, and enhances the connectivity of pores and fissures, thus allowing methane‐producing bacteria to enter the coal mass and create favorable conditions for gas production through interactions between the two. X‐ray photoelectron spectroscopy measurements showed that the secondary gas production increased the C content on the coal surface, decreased the O content and the O/C ratio, thus promoting the consumption of oxygen‐containing functional groups on the coal surface to further produce gas. Abstract : 1. The biogas production capacity of residual coal extracted by NMP and acetone was enhanced; gas production efficiency of primary residual coal is reduced. 2. Solvent extraction loosens the macromolecular network structure, allowing methane‐producing bacteria to enter the coal mass and create favorable conditions for gas production. 3. The secondary gas production increased the C content on the coal surface, decreased the O content and the O/C ratio, promoting the consumption of oxygen‐containing functional groups on the coal surface to further produce gas.